From catch-up TV to online TV: digital broadcasting and the case of BBC iPlayer - Grainge, Paul; Johnson, Catherine (Oxford University Press, 2016)
This article examines the ways in which the on-demand service BBC iPlayer became a site for navigating what it means to be a public service broadcaster in a hybrid TV-digital world. Focusing on a key period of transition for the BBC - bracketed by the publication of the BBC’s strategy document Delivering Quality First (2011) and the anticipation of charter review in 2016 - we consider how BBC iPlayer helped mobilize a set of managerial discourses that informed thinking about the BBC’s online proposition in an age of public service media. Specifically, we argue that a new version of iPlayer, launched in 2014, can be understood as a staging point in the BBC’s attempt to understand and rationalise its role as a digital broadcaster. Reconceived from a catch-up service to an entertainment destination, we examine how the ‘new iPlayer’ catalysed thinking about the meaning of online television - from the internal implications for online commissioning practice and content curation to the broader managerial vision of ‘reinventing public service broadcasting through data’. Informed by critical media industry studies, the article draws on practitioner interviews with senior BBC managers and industry documents to consider the ‘discourses, dispositions and tactics’ that coalesced around BBC iPlayer in a moment when the Corporation was striving to recalibrate its identity, digital content offer, and sense of relevance in a period where distinctions between broadcasting and online were becoming, and remain, increasingly blurred.